Memory in Times of Crisis (KULT_online, 2010)
Fragmentary memories, traumas and false versions of one’s past – these are the starting points for Dorothee Birke’s dissertation on memory crises. Within a field of investigation that has recently been concerned with deformation and modification of memories, Birke takes a closer look at the representation of memory crises in literary texts. She investigates the staging of memory crises both from a synchronic and from a diachronic point of view. By using cognitive narratology she develops a tool box to investigate two novels by Charles Dickens and Virgina Woolf. Applying her results to four contemporary British novels she demonstrates how these refer to and modify well-known models. This shows that the representation of memory processes in literature is always connected to a certain historical situation – in this case, a time in which autobiographical memories turn into crises.